2013
DOI: 10.5812/pedinfect.14373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition Among Under-Five Year Old Children With Acute Lower Respiratory Tract Infection Hospitalized at Udupi District Hospital

Abstract: Background: Increased incidence and severity of acute lower respiratory tract infection (ALRI) are variably associated with malnutrition. Objectives: We aimed to examine the prevalence of malnutrition in under-five year old hospitalized children with ALRI. Patients and Methods: Children aged from 6 to 60 months, mostly from a low socioeconomic population, admitted with ALRI, were enrolled prospectively. WHO case definition was used for ALRI. The data about the weight, length/height, mid-arm circumference (MAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Children who had suffered more than 3 episodes of ARI in the last 1 year had higher prevalence of under-nutrition which was statistically significant. Similar findings were observed in a study by Ramesh et al and Chhabra et al 9,10 Use of kerosene as the major source of cooking fuel which is a known risk factor for ARI was also found to be significantly associated with the prevalence of undernutrition.…”
Section: Discussionsupporting
confidence: 88%
“…Children who had suffered more than 3 episodes of ARI in the last 1 year had higher prevalence of under-nutrition which was statistically significant. Similar findings were observed in a study by Ramesh et al and Chhabra et al 9,10 Use of kerosene as the major source of cooking fuel which is a known risk factor for ARI was also found to be significantly associated with the prevalence of undernutrition.…”
Section: Discussionsupporting
confidence: 88%
“…The most common age group in the study was 1-4 years with male preponderance which is on par with findings of Yellanthoor RB et al who reported similar pattern of prevalence in his study and male to female ratio. 6 LRTI was most common in children belonging to low socioeconomic status, which is also added by many risk factors like overcrowding, malnutrition, absence of immunization etc which are more commonly observed in low socio-economic group. The incidence of LRTI in our study among low socioeconomic group was 73.65% which is similar to findings of Kabra SK, Broor S et al 7 PEM-I was observed in 35.20% with maximum in female children than males, in 1-4 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 110 cases in the study group, malnutrition was observed in 64 (58.18%) cases which is closer to the results reported by Bhat R et al (54.9%). 6 Out of 63 cases in Pneumonia group, 35 (55.55%) cases were malnourished with weight < 3 percentile. Out of 47 cases in the severe pneumonia group, 29 (61.70%) children were malnourished with weight less than 3 rd percentile.…”
Section: Resultsmentioning
confidence: 91%
“…This is similar to the studies done by Ramachandran et al and Bhat R et al where they have reported 58% boys and 42 % girls. 2,6 Whereas Divyarani DC et al in their study reported a higher incidence of pneumonia in males (62.6%) than in females (37.4%). 5 ď‚· Cases 0-3 years of age show significantly higher proportion of severe pneumonia with p value <0.02 ď‚· The proportion of pneumonia and severe pneumonia in males and females is similar ď‚· Though 'P' value is not significant, the proportion of Severe Pneumonia is significantly higher in malnourished cases with weight for age <3 percentile ď‚· The proportion of severe pneumonia is significantly higher in not exclusively breast fed babies with P value < 0.05 ď‚· The proportion of severe pneumonia is significantly higher in not fully vaccinated group with P value <0.05 ď‚· Though 'p' value is not significant, the proportion of severe pneumonia is higher in cases with duration of hospital stay more than 1week.…”
Section: Resultsmentioning
confidence: 91%